การพัฒนาอัลกอริทึมสำหรับการตรวจสอบอะแดพเตอร์การ์ด - ตั้งดี, บวร; มุณีสว่าง, ไพศาล; แย้มเม่น, สุชาติ (Naresuan University Engineering Journal, 2014)
บทความนี้นำเสนอการพัฒนาขั้นตอนการตรวจหาเม็ดโฟม ของภาพอะแดพเตอร์การ์ด วิธีการตรวจหาเม็ดโฟมที่นำเสนอมี 3 ขั้นตอน คือ (1) ขั้นตอนการสร้างภาพต้นฉบับอะแดพเตอร์การ์ด (2) ขั้นตอนการเตรียมข้อมูลภาพที่นำมาทดสอบซึ่งประกอบด้วยการเลือกบริเวณที่น่าสนใจ การปรับค่าระดับกำลังของภาพให้เท่ากันและการแปลงเป็นภาพ ไบนารีด้วยวิธีโอซึ และ (3) ขั้นตอนการตรวจสอบสภาพของ อะแดพเตอร์การ์ดด้วยการหาเม็ดโฟมซึ่งประกอบด้วยการลบภาพที่นำมาทดสอบด้วยภาพต้นฉบับ การติดฉลากและเชื่อมต่อพิกเซลวัตถุที่ติดต่อกันเพื่อหาตำแหน่งของเม็ดโฟม การกรองสัญญาณรบกวนและการใช้ค่าขีดแบ่งในการตัดสินใจ จากผลการทดลอง พบว่าประสิทธิภาพสูงสุดในการตรวจหาเม็ดโฟม ของขั้นตอนที่นำเสนอเกิดขึ้นเมื่อเลือกจำนวนพิกเซลวัตถุที่เชื่อมติดกันที่ตำแหน่งมากกว่า 25 พิกเซล เลือกองค์ประกอบโครงสร้างรูปสี่เหลี่ยมจัตุรัสขนาด 4x4 พิกเซล2 และกำหนดค่าขีดแบ่งเท่ากับ 111.50 โดยมีค่าตัวชีวัดประสิทธิภาพทั้งสี่ ดังนี้ ความไวมีค่าเท่ากับ 98.46% ความจำเพาะมีค่าเท่ากับ 96.00% ความถูกต้องมีค่าเท่ากับ 96.00% และความแม่นยำมีค่าเท่ากับ 88.89% Algorithm Development for Investigating Adapter Cards This paper presents the algorithm development for detecting the Styrofoam beads in the adapter card image. The proposed method has three steps: (1) the process of constructing the template image of the adapter card, (2) the process of preparing testing images, which includes with selecting region of interest, adjusting the power level of the image and converting the testing image into a binary image by using the Otsu method, and (3) the process of detecting the Styrofoam beads, which includes with subtracting the testing image with the template image, labeling and connecting objects pixels in order to determine the location of the Styrofoam beads, filtering noise and using the threshold value in the decision making process. From experimental results, these show that the most satisfactory result for detecting the Styrofoam beads of the proposed algorithm occurs when the number of pixels for the connected object position is more than 25 pixels, the structure element is a square of 4 x 4 pixels, and the threshold value is equal to 111.50. In addition, the efficiency of proposed method provides the four following quantitative measures. The value of the sensitivity is equal to 98.46%, the value of the specificity is equal to 96.00%, the value of the accuracy is equal to 96.60%, and the value of the precision is equal to 88.89%.